2021
DOI: 10.3389/fpls.2021.748209
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptomics and Metabolomics Analyses Provide Insights Into the Response of Chongyi Wild Mandarin to Candidatus Liberibacter Asiaticus Infection

Abstract: Candidatus Liberibacter asiaticus (CLas) is the causative agent of Huanglongbing (HLB), which has caused great economic losses to the citrus industry. The molecular mechanism of the host response to CLas in wild citrus germplasm has been reported less. Eighteen weeks after inoculation via grafting, all the CLas-inoculated Chongyi wild mandarin (Citrus reticulata) were positive and showed severe anatomical aberrations, suggesting its susceptibility to HLB. Transcriptomics and metabolomics analyses of leaves, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 79 publications
(92 reference statements)
1
8
0
Order By: Relevance
“…Overall, most of the metabolites in the pathway of carbon fixation in photosynthetic organisms were downregulated, and those distributed in other pathways were upregulated (see Figure 2 and Supplementary Data S3 ). This result is quite consistent with the previous reports [ 19 , 39 45 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Overall, most of the metabolites in the pathway of carbon fixation in photosynthetic organisms were downregulated, and those distributed in other pathways were upregulated (see Figure 2 and Supplementary Data S3 ). This result is quite consistent with the previous reports [ 19 , 39 45 ].…”
Section: Resultssupporting
confidence: 94%
“…As shown in Figure 4a , six metabolites located on the pathway of carbon fixation in photosynthetic organisms, including pyruvate, L-alanine, L-aspartate, L-phenylalanine, phenylpyruvate and sedoheptulose were detected to be significantly downregulated in the infected group compared to the healthy group. Peng et al [ 39 ] reported that the leaves of “Chongyi” wild mandarin ( Citrus reticulata ) showed downregulation of transcripts and metabolites relevant to carbon fixation after 18 weeks of graft-inoculation with Ca Las-infected buds by the integrated transcriptomics and metabolomics analyses. Wei et al [ 40 ] also reported that the number of differentially expressed genes (DEGs) related to photosynthesis detected in “Valencia” orange ( C. sinensis ) at one and five days of post- Ca Las-infected psyllid infection was greatly less than that of healthy psyllid infection.…”
Section: Resultsmentioning
confidence: 99%
“…Sugars not only provide energy for plants’ growth and defense responses, but also act as signals in modulating plants’ adaptation to internal and external stimuli, including invading pathogens. Several of the previous investigations have revealed that the level of different types of sugars were altered in the HLB-infected tissues, such as leaves, barks, roots, and fruits, but the trend varied depending on the variety, tissues, and disease progression [ 17 , 22 , 30 , 42 , 43 , 44 ]. Generally, the sugar contents were decreased after infection.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the sugar contents were decreased after infection. Peng et al [ 22 ] explored the metabolomic changes of the Chongyi wild mandarin in the positive- or mock-inoculated plants. The sucrose levels were increased in both the infected leaves and barks, but did not change in the roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation